2023
DOI: 10.3390/electronics12030749
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Augmented Reality (AR) on Vocabulary Acquisition and Student Motivation

Abstract: Although there is a growing body of literature about the use of Augmented Reality (AR) in language learning, research regarding its effectiveness for vocabulary development among secondary students is scarce. This study aims to measure the perception toward AR technology (H1), the effect of its use on vocabulary development (H2), and its impact on student motivation (H3). In this mixed method research based on convenient sampling, 130 students aged 14 to 15 (9th-graders) from two secondary education schools we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The findings revealed significant interest in AR integration among students. However, no significant differences were observed in vocabulary learning performance between the experimental and control groups [45].…”
Section: Ar/vr For K-12 Educationmentioning
confidence: 72%
“…The findings revealed significant interest in AR integration among students. However, no significant differences were observed in vocabulary learning performance between the experimental and control groups [45].…”
Section: Ar/vr For K-12 Educationmentioning
confidence: 72%
“…The findings highlighted the students' strong positive attitude towards AR technology and their high motivation to use it for learning. Belda‐Medina et al [6] conducted a study on the impact of AR on cognition, vocabulary learning, and student motivation. The research findings demonstrated that using AR for language learning sparked positive attitudes and strong interest among students.…”
Section: Related Workmentioning
confidence: 99%
“…Extended Reality (XR), including Augmented Reality (AR) and Virtual Reality (VR), enhances the user's visual experience [8,9], provides immersion, and motivates students through innovative learning approaches [10,11]. Nevertheless, educational experiments developed with XR do not provide real data, since they are, in principle, based on mathematical logical models.…”
Section: Introductionmentioning
confidence: 99%